1989
DOI: 10.1128/jb.171.9.5048-5055.1989
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of five genes in the upper-pathway operon of TOL plasmid pWW0 from Pseudomonas putida and identification of the gene products

Abstract: The upper operon of the TOL plasmid pWW0 of Pseudomonas putida encodes a set of enzymes which transform toluene and xylenes to benzoate and toluates. The genetic organization of the operon was characterized by cloning of the upper operon genes into an expression vector and identification of their products in Escherichia coli maxicells. This analysis showed that the upper operon contains at least five genes in the order of xylC-xylM-xylA-xylB-xylN. Between the promoter of the operon and xylC, there is a 1.7-kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 28 publications
5
108
0
Order By: Relevance
“…The organization of the genes encoding the enzymes of the benzyl alcohol pathway in A. calcoaceticus is different from that of the TOL-plasmid pWW0 since the latter has an operon with additional genes [3,4]. In the TOL-system, genes are transcribed in the order xylUWCMABN where xylU encodes a small protein consisting of 131 amino acid residues, but has no significant identity with any known protein sequences, and xylW encodes a 341 amino acid protein that is homologous with members of the long-chain zinc-dependent alcohol dehydrogenases.…”
Section: A Calcoaceticusmentioning
confidence: 99%
See 2 more Smart Citations
“…The organization of the genes encoding the enzymes of the benzyl alcohol pathway in A. calcoaceticus is different from that of the TOL-plasmid pWW0 since the latter has an operon with additional genes [3,4]. In the TOL-system, genes are transcribed in the order xylUWCMABN where xylU encodes a small protein consisting of 131 amino acid residues, but has no significant identity with any known protein sequences, and xylW encodes a 341 amino acid protein that is homologous with members of the long-chain zinc-dependent alcohol dehydrogenases.…”
Section: A Calcoaceticusmentioning
confidence: 99%
“…As yet, these two proteins have no known function. Gene xylC encodes benzaldehyde dehydrogenase, xylM and xylA encode the two subunits of xylene monoxygenase, xylB encodes benzyl alcohol dehydrogenase and xylN encodes another polypeptide of unknown function [4]. The fact that xylM and xylA are absent from A. calcoaceticus is not surprising since this organism is not able to degrade toluene and toluates [20].…”
Section: A Calcoaceticusmentioning
confidence: 99%
See 1 more Smart Citation
“….xylCAB and the operator-promoter (OPI) are as determined by Keil et al (1987~). It is assumed that there is a gene corresponding to xylM as has been determined for pWW0 (Harayama et al, 1989). Similar restriction sites in each have been linked with dotted lines.…”
Section: Identijcation Of Two Upper Pathway Operonsmentioning
confidence: 99%
“…Whereas most of the molecular biology of the catabolic pathway has been characterized on the 117 kbp plasmid pWW0 from Pseudomonasputida mt-2, a number of other plasmids encoding the same catabolic functions have been described (see Assinder & Williams, 1990). There is an increasing amount of evidence which suggests that the genetic organization of the xyl catabolic genes found on pWW0, namely single operons for the upper pathway (Harayama et a/., 1989) and the meta pathway genes (Harayama & Rekik, 1990), is not typical of many of these other plasmids. Chatfield & Williams (1986) showed that newly isolated plasmids contained either two homologous genes or two nonhomologous genes for the ring-cleavage dioxygenase, catechol 2,3-dioxygenase (C230, xylE).…”
Section: Introductionmentioning
confidence: 99%